Torture Moral Absolutes and Ambiguities (Volume 2) - Clucas, Bev; Johnstone, Gerry; Ward, Tony (Nomos Verlagsgesellschaft mbH & Co. KG, 2009)
Not so long ago, the only respectable question for philosophical, legal, and political scholars to ask about torture was how to ensure its effective legal prohibition. Recently, however, some leading lawyers and legal theorists have challenged those who are absolutely opposed to torture, arguing that, in some circumstances, torture may be morally permissible or even required. This has provoked a range of responses, from outraged dismissal to cautious concessions that the law has to adjust to new realities. This volume contains writings by some of the leading contributors to these debates. Distinctively, it supplements the discussion about the morality of torture - and the morality of discussing torture - with essays which provide important legal, sociological, and historical analyses of this appalling human practice and of the attempts to control it. With an international and interdisciplinary authorship, Torture: Moral Absolutes and Ambiguities will be essential reading for legal and political theorists, philosophers, sociologists, historians, and indeed anybody interested in serious and informed thinking about this most disturbing phenomenon.